Financial Performance Determinants: Sustainability Reporting, CSR, Environmental Performance, and Green Innovation in Indonesian Manufacturing Firms - Dewi Maryati; Herlin Tundjung Setijaningsih (International Journal of Applied Business and International Management, 2026)
Manufacturing firms in emerging economies face growing pressure to balance profitability and sustainability, yet their financial outcomes remain inconclusive. This study aims to examine the effects of sustainability reporting (SR), corporate social responsibility (CSR), and environmental performance (EP) on the financial performance (FP) of Indonesian manufacturing firms during 2020–2024, while investigating the moderating role of green innovation (GI). Using a quantitative panel-data design with purposive sampling, data from 42 manufacturing firms (210 firm-year observations) were analyzed using multiple linear regression in STATA 17. The Common Effect Model (R² = 0.2707) indicates that SR (b = 1.162, p = 0.024), CSR (b = 3.363, p = 0.047), and GI (b = 6.090, p = 0.039) have significant positive effects on FP, whereas EP has a positive but insignificant effect (p = 0.583). Furthermore, GI negatively moderates the relationships between SR and FP (b = ?30.809, p = 0.006) and between EP and FP (b = ?6.206, p = 0.015), while its moderating effect on the CSR–FP relationship is insignificant (p = 0.619). These findings suggest that firms should strategically balance green-technology investment and sustainability initiatives to manage potential short-term resource trade-offs while pursuing long-term financial performance.